2017
DOI: 10.3892/ol.2017.5708
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling is important for epithelial-mesenchymal transition induced by low concentrations of doxorubicin in osteosarcoma cell lines

Abstract: Osteosarcoma is an aggressive pediatric tumor affecting growing bones that typically occurs in adolescents and young adults. Although advances in treatment have been made in recent years, a high proportion of patients relapse due to metastases, which are frequently resistant to chemotherapy and pose a significant threat to long-term survival. Previous studies have demonstrated that the epithelial-mesenchymal transition (EMT) is associated with cancer occurrence and metastasis, and our previous study demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…This progression can be triggered by various developmental signalling pathways, such as tumour growth factor beta, Wnt, Notch, growth factor receptor tyrosine kinases and PLC-γ pathways [25]. Notch signalling is an evolutionarily conserved pathway involved in EMT and metastasis [29][30][31][32][33]. In mammals, Notch signalling includes four transmembrane Notch receptors (Notch-1, Notch-2, Notch-3 and Notch-4) and five canonical transmembrane ligands (Delta-like DLL1,DLL3, DLL4, Jagged-1 and Jagged-2) [34].…”
Section: Mir-184 Inhibits Npc Metastasis By Decreasing Emt In Vivomentioning
confidence: 99%
“…This progression can be triggered by various developmental signalling pathways, such as tumour growth factor beta, Wnt, Notch, growth factor receptor tyrosine kinases and PLC-γ pathways [25]. Notch signalling is an evolutionarily conserved pathway involved in EMT and metastasis [29][30][31][32][33]. In mammals, Notch signalling includes four transmembrane Notch receptors (Notch-1, Notch-2, Notch-3 and Notch-4) and five canonical transmembrane ligands (Delta-like DLL1,DLL3, DLL4, Jagged-1 and Jagged-2) [34].…”
Section: Mir-184 Inhibits Npc Metastasis By Decreasing Emt In Vivomentioning
confidence: 99%
“…Nonetheless, the underlying mechanisms by which tobacco smoke induces EMT and the signaling events that underlie EMT are poorly understood. Notch signaling regulates a series of cellular processes (21). Several studies have revealed that Notch pathway is critically involved in the process of EMT (21,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Notch signaling regulates a series of cellular processes (21). Several studies have revealed that Notch pathway is critically involved in the process of EMT (21,23,24). To examine the role of Notch pathway in tobacco smoke-induced EMT, we addressed the relationship between Notch and gastric EMT induced by tobacco smoke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations